Release, Aggregation and Lysis of Human Platelets by Antilymphocyte Globulin and Antiplatelet Serum - Lekas, Nicholas; Rosenberg, J. C (Thrombosis and Haemostasis, 1976)
Human platelets labeled with 51Cr were used to determine the contribution made by platelet lysis to the platelet release reaction and platelet aggregation induced by rabbit antihuman platelet serum (APS) and equine antihuman thymocyte globulin (ATG). Platelets were tested in both plasma (PRP) and non-plasma containing media. Antibodies directed against platelets, either as APS or ATG, induced significant amounts of platelet release and aggregation, as well as some degree of lysis, in the absence of complement. The presence of complement increased platelet lysis and aggregation, but not the release reaction. Non-immune horse gamma globulin produced different responses depending upon whether platelets were investigated in PRP or non-plasma containing media. Aggregation was seen in the latter but not the former. These differences can be explained by the presence of plasma components which prevent non-specific immune complexes from causing platelet aggregation. Since platelets in vivo are always in a plasma medium, one must be wary of utilizing data from platelet studies in synthetic plasma-free media as the basis of explaining clinical events. These observations demonstrate at least two, and possibly three, different mechanisms whereby ATG could activate platelets causing thrombotic complications and thrombocytopenia, i.e., via 1) specific and, 2) non-specific non-lytic pathways and 3) a lytic pathway.